Carbon sink and greenhouse gas emission of dryland vegetation cover in tourism villages in Flores Island, East Nusa Tenggara, Indonesia - FATMA LESTARI; INDRA NI TUA; ADONIS MUZANNI; DANESTA FEBIANTO NUGROHO; ANDRIO A. WIBOWO; TRI WARTONO; BAIDURI WIDANARKO; ASEP SAEPULLAH; ROBIANA MODJO; MIFTACHUL FARIDA; DADAN ERWANDI; DESSY DWI ARYANI; ABDUL KADIR; ANINDHITA IRSALINA WIDIATMOKO; HENDRA HENDRA; ZICO JUNI HERWANTO; MILA TEJAMAYA; RIZAL ALFIANSYAH HAMID; FATMAH FATMAH; EZSA LARASHATI GUNAWAN; DINA LUSIANA SETYOWATI; M. FAIZIR HAFIDS; ROSSI YULIANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lestari F, Tua IN, Muzanni A, Nugroho DF, Wibowo AA, Wartono T, Widanarko B, Saepullah A, Modjo R, Farida M, Erwandi D, Aryani DD, Kadir A, Widiatmoko AI, Hendra, Herwanto ZJ, Tejamaya M, Hamid RA, Fatmah, Gunawan EL, Setyowati DL, Hafids MF, Yuliani R. 2023. Carbon sink and greenhouse gas emission of dryland vegetation cover in tourism villages in Flores Island, East Nusa Tenggara, Indonesia. Biodiversitas 24: 1998-2005. Due to its natural features and scenery, the dryland ecosystem has recently become a tourist destination. One of the growing dryland ecosystems for village tourism is Flores Island, East Nusa Tenggara, Indonesia. Those tourism villages have the potential to promote carbon sequestration through the preservation of natural resources and, at the same time, can release Green-House Gases (GHG). Despite growing research on carbon stock, there is little information on the carbon budget of a dryland tourism village, which includes the values of carbon stock sequestered from the atmosphere and greenhouse gas emissions. This research aimed to measure the carbon stock and GHG emissions in three villages containing paddy fields, savanna, and forest covers. The measured gases, including CO2, CH4, and N2O, were collected using the gas chamber method and analyzed using gas chromatography. The result shows that forest land covers have the highest carbon stock, with average values of 97.44 Mg ha-1 within the 57.34-117.5 Mg ha-1. A low average carbon stock of 17.39 Mg ha-1 was observed in paddy fields. The GHG was in the order of CO2 > CH4 > N2O. The paddy field has higher GHG than other land covers, with average CO2, CH4, and N2O values of 292.45 ppm, 1.35 ppm, and 1.09 ppm. While CO2, CH4, and N2O values for the forest were 281.05 ppm, 1.30 ppm, 1.05 ppm, 272.83 ppm, 1.26 ppm, and 1.02 ppm for savanna covers.